A modified cavity slide for temporary preparation and illustration of insect genitalia in glycerin - Ament, Danilo César (Zootaxa, 2015)
The taxonomy of most groups of insects is largely dependent on genitalic characters, which can be extremely complex, even asymmetric (Huber et al. 2007). The study of small, complex insect terminalia, then, often requires microscopic examination of this structure in more than one view, using temporary slide mounting. The temporary mounting generally consists of the placement of the structure in a cavity slide filled with glycerin or glycerin jelly with a cover slide. The preparation in glycerin may be faster than in glycerin jelly if the problem of stabilizing the structure in the correct position can be overcome.